The relation between social capital, governance and economic performance in Europe - Jankauskas, Vidmantas; Šeputienė, Janina (Business: Theory and Practice, 2007)
The literature on social capital stresses the relations between social capital (trust, social norms and networks), government effectiveness and economic performance. In empirical investigations the relationship between aforementioned items was clarified by using various indicators of social capital and different country samples. Due to this reason the results are hardly comparable. In this article we aim to examine the strength of the relationship between social capital, governance quality and economic performance by using the same indicators of social capital and the same country sample (23 European countries). The study has indicated that both social capital and government indicators are related to economic performance and to each other. Results showed the positive correlation of two social capital dimensions, namely trust and networks, with economic performance indicators and governance indicators, while civism dimensions do not correlate either with economic performance or with governance indicators. In this paper we used three economic performance indicators, namely GDP per capita in Purchasing Power Standards, labour productivity per person employed and percentage of gross domestic expenditure on R&D (GERD) financed by industry.